The Religious Political Identity of Kaum Sayid in the Ziarah Kubra Tradition in Palembang - Syukri, Ahmad (UIN Sunan Gunung Djati Bandung, 2022)
Ziarah Kubra is a religious tradition that developed in Palembang in an atmosphere of the revival of the spirit of Islamic diversity in Indonesia in the millennial period. The Ziarah Kubra tradition began to be popularized in 2003 by the Kaum Sayid in Palembang. The Kaum Sayid or Sayids is a community descended from the Prophet Muhammad (PBUH), who traveled worldwide, including Palembang.This article discusses the Ziarah Kubra tradition's phenomenon towards constructing the Kaum Sayid's religious identity in Palembang. The research study in this article uses qualitative research methods with a phenomenological approach to the Ziarah Kubra tradition in Palembang. The Ziarah Kubra was originally a local religious practice of the Kaum Sayid in Palembang, which continued to develop into the collective religious identity of Islamic civilization in Indonesia. The construction of the religious-political identity of the Kaum Sayid in Palembang was formed, along with the acceptance and recognition of other communities and local elites to the religious authority of the Kaum Sayid in Palembang in the Ziarah Kubra tradition. This article shows that a religious tradition can be an institution of a local community's religious-political identity.